2007
DOI: 10.1016/j.amepre.2007.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Seat Belt Use Among American Indians/Alaska Natives and Non-Hispanic Whites

Abstract: Background-Accidents (including motor vehicle accidents) are a leading cause of death among American Indians/Alaskan Natives (AI/AN). The purpose of this study was to examine geographic variation and the existence of a seatbelt law on seatbelt use among AI/AN and non-Hispanic Whites (NHW).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Data on socio-demographic characteristics of drivers and passengers in the car as the behaviour predictors which influence the degree of use of seat belts in Bosnia and Herzegovina, or some other predictors such as road and mood predictors based on the observed sample and on the self-reported behaviour of examinees in traffic, have proven to be important variables. These results correspond to previous studies where it was found that the participants' views and subjective norms are important predictors of the intended behaviour [29][30][31][32][33][34].…”
Section: Discussionsupporting
confidence: 91%
“…Data on socio-demographic characteristics of drivers and passengers in the car as the behaviour predictors which influence the degree of use of seat belts in Bosnia and Herzegovina, or some other predictors such as road and mood predictors based on the observed sample and on the self-reported behaviour of examinees in traffic, have proven to be important variables. These results correspond to previous studies where it was found that the participants' views and subjective norms are important predictors of the intended behaviour [29][30][31][32][33][34].…”
Section: Discussionsupporting
confidence: 91%
“…Seat belt and child restraint use among black adults and children are lower than the national average. 4,5 Similarly, seat belt use among Hispanic (85%) and non-Hispanic black (80%) adults traveling with children was lower than that for white (96%) adults traveling with children. 6 The reasons for these disparities in restraint use are not completely known but may be related to a lack of knowledge as well as a lack of culturally appropriate messages from generalized public education intervention programs.…”
mentioning
confidence: 99%
“…However, disparities continue to exist, with special focus needed to develop evidence-based interventions to improve BPB use among non-white populations. Hispanic and non-Hispanic black children use child restraints at lower rates than white children (Daniels et al 2002;Garcia et al 2007;Pickrell and Ye 2009b). Previous studies indicated that low rates of BPB use are related to differences in risk perception, awareness, knowledge, and parenting styles (Simpson et al 2002).…”
Section: Introductionmentioning
confidence: 97%